Transformer-based biomarker prediction from colorectal cancer histology: A large-scale multicentric study - Wagner, Sophia J.; Reisenbüchler, Daniel; West, Nicholas P.; Niehues, Jan Moritz; Zhu, Jiefu; Foersch, Sebastian; Veldhuizen, Gregory Patrick; Quirke, Philip; Grabsch, Heike I.; van den Brandt, Piet A.; Hutchins, Gordon G.A.; Richman, Susan D.; et al. (Cancer Cell, 2023)
Deep learning (DL) can accelerate the prediction of prognostic biomarkers from routine pathology slides in colorectal cancer (CRC). However, current approaches rely on convolutional neural networks (CNNs) and have mostly been validated on small patient cohorts. Here, we develop a new transformer-based pipeline for end-to-end biomarker prediction from pathology slides by combining a pre-trained transformer encoder with a transformer network for patch aggregation. Our transformer-based approach substantially improves the performance, generalizability, data efficiency, and interpretability as compared with current state-of-the-art algorithms. After training and evaluating on a large multicenter cohort of over 13,000 patients from 16 colorectal cancer cohorts, we achieve a sensitivity of 0.99 with a negative predictive value of over 0.99 for prediction of microsatellite instability (MSI) on surgical resection specimens. We demonstrate that resection specimen-only training reaches clinical-grade performance on endoscopic biopsy tissue, solving a long-standing diagnostic problem.
CRIS-Team Scopus Importer:2023-09-15
Keywords: artificial intelligence; biomarker; colorectal cancer; deep learning; microsatellite instability; multiple instance learning; transformer